Pond Geographic Information System Polygon Geometry Web Based at Pohuwato Regency Office - Abdul Malik I Buna; Bahtiar Senung; Abdul Rahman Ismail (STMIK Budi Darma, 2021)
The large number of pond owners using land that is already included in protected forest areas and nature reserve areas has made it difficult for officers to obtain information on the tax objects for pond cultivation. Geographical Information System Application for Tambak Web Based Geometry Polygon at the Pohuwato Fisheries Service which is integrated directly with the internet. The goal is to make it easier for the officers and owners of the pond to find out information about the area of the pond and the taxes payable periodically automatically directly from the website. The research method uses the Waterfall method. Take basic activities such as specification, development, validation, and evolution and represent them as different process phases such as requirements specification, software design, implementation, testing and so on. This application will be developed for the desktop with a web-based operating system. There are two programming techniques used, the client side will use Java programming and the server side will use PHP Programing